Self‐Normalized Detection of ANXA3 from Untreated Urine of Prostate Cancer Patients without Digital Rectal Examination. Issue 17 (13th July 2017) - Jeun, Minhong; Park, Sungwook; Kim, Yongdeok; Choi, Jaewon; Song, Sang Hoon; Jeong, In Gab; Kim, Choung‐Soo; Lee, Kwan Hyi
Abstract : A noninvasive quantitative assay that is capable of identifying prostate cancer biomarkers in untreated urine is an attractive diagnosis tool, but this method is subject to various obstacles. Difficulties presented by untreated urine include varying salt concentrations, and pH levels that may be different even though they are from the same patient. Untreated urine also presents interference from other biomolecules and possesses a fewer number of cancer biomarkers than can be found in serum. As a result, urine preconditioning processes and digital rectal examination (DRE) to increase biomarker secretion are mandatory in current urine assays. To address these challenges, an ion‐responsive urine sensor (IRUS) that measures differential electrical signals is proposed as a self‐normalized detection method. The proposed IRUS is based on a FET biosensor with a disposable sensing gate and has the capability to detect the prostate cancer antigen ANXA3 in untreated patient urine. The IRUS can detect ANXA3 at <1 fg mL −1 with high reliability. In addition, it is found that ANXA3 levels in urine show clinically significant correlation with real tumor volumes. This paper provides a guideline in developing a clinically ready accurate noninvasive platform, which is capable of predicting prostate cancer using untreated urine without DRE. Abstract : The IRUS (ion‐responsive urine sensor) proposed is capable of quantitative analyzing minuscule amounts of prostate cancer biomarkers from untreated patient's urine samples by self‐normalizing method. The IRUS has a low limit of detection (≈1 fg mL −1 ) as well as high reliability and sensitivity. The quantitative analysis of the biomarkers is useful to predict the prostate tumor volume of the patients.